Pengaruh Kompensasi Terhadap Kinerja Karyawan Dimediasi Kepuasan Kerja Karyawan - Try Chairunisyah Lubis; Fajar Pasaribu; Zulaspan Tupti (CERED Indonesia Institute, 2021)
The purpose of this study was to determine the effect of compensation on employee performance mediated by employee job satisfaction at Bank Syariah Mandiri Ahmad Yani Branch Medan. This study uses a quantitative approach. The study population was all employees who worked at Bank Syariah Mandiri Ahmad Yani Medan Branch. The research sample was all employees at Bank Syariah Mandiri Ahmad Yani Medan, totaling 75 people. This study uses validity and reliability tests. The data analysis used is the Structural Equation Model (SEM) method with the Partial Least Square (PLS) method. The results of this study indicate that: (1) Compensation has a significant positive effect on employee performance with a value of 0.488 and P-Values of 0.000. (2). Job Satisfaction has a significant positive effect on Employee Performance through Employee Job Satisfaction with a value of 0.369 and P-Values of 0.000. (3). Compensation has a significant positive effect on Job Satisfaction with a value of 0.781 and P-Values of 0.000. (4). Compensation has a significant positive effect on Employee Performance through Employee Job Satisfaction with a value of 0. 228 and P-Values of 0.000.